An improved stanley guidance law for large curvature path following of unmanned surface vehicle - Yang, Xiaofei; Yan, Xin; Liu, Wei; Ye, Hui; Du, Zhaoping; Zhong, Weibo (Ocean engineering, 2022)
In order to enhance the large curvature path following performance of unmanned surface vehicle (USV), an improved Stanley guidance law (ISGL) is proposed. To the best of our knowledge, we are the first to introduce the Stanley guidance law (SGL) to guidance subsystem of USV, and theoretically prove that it can be unified into one form with the line-of-sight (LOS). It is essentially a kind of LOS method with time-varying lookahead distance in the path-tangential reference frame. For the sake of accurately following the path with large curvature, a compensation angle (km/(1+|ye|))Δαm is integrated to improve the original SGL, which can evaluate the path curvature in advance and compensate the desired heading angle. The aim is to improve the heading angle error and make USV turn in advance. In order to verify path following performance of our algorithm, theoretical simulation and lake experiments are launched to compare to extended line-of-sight (ELOS), integral line-of-sight (ILOS) and original SGL algorithms. All the results show that our ISGL algorithm has better path following performance than others. •We have proved theoretically for the first time that Stanley guidance law is equivalent to be LOS with time-varying look-ahead distance in the path-tangential reference frame.•Stanley guidance law is improved and introduced to the guidance subsystem of USV to advance the large curvature path tracking accuracy.•ELOS, ILOS and SGL are adopted to compare with our ISGL. Results show the advantages in large curvature path.